REJUVENATING THE DWINDLING IMAGE OF ORANGE GROVE THROUGH THE APPLICATION OF PLACE BRANDING TECHNIQUES - Harding, Dean (The IIE, 2018)
Orange Grove has faced a general decline over the last 25 years. This research report looks at finding workable place branding techniques and strategies that could rejuvenate the image of Orange Grove. The primary research method was photographic ethnography. Two large panoramas were created and formed the framework of the visual analysis. The findings highlighted the need for a community noticeboard or pause area. An extremely vibrant and productive informal sector exists, with 10 groups of vendors and a number of places of worship. The general aesthetic of the area is not as bad as originally thought and the places of worship could be used as a draw card to bring people in from other areas and hopefully spend some money in the neighbourhood. Gentrification is real and we should all guard against the devastating effects it has on marginalised communities. More design thinking and design solutions are needed to help the informal sector find ways of generating more money and being able to become self-sustaining.
Keywords: Place branding; Visual design; Photographic ethnography; Informal sector; Informal settlements; Gentrification